HIGH-PT STUDY OF SOLID SOLUTIONS IN THE SYSTEM ZRO2-TIO2: THE STABILITY OF SRILANKITE - Troitzsch U.; Ellis D.J. (My University, 2004)
The ZrO 2-TiO2 phase diagram was studied with synthesis experiments between 1200°C and 1650°C, 1 atm and 28 kbar, investigating the effect of pressure on the compositions of rutile [TiO2], zirconia [ZrO2], and zirconium titanate [(Zr, Ti) 2O4] solid solutions. All three phases become more Ti-rich with increasing pressure, which is in good agreement with the smaller ionic radius of Ti 4+ compared to Zr 4+ , and consistent w ith the observed unit-cell volume of (Zr, Ti)2 O4. The range of zirconium titanate solid solution, which is limited to XTi < 0.58 at room pressure, was extended to xTi = 0.68 at 28 kbar and 1500°C. Thus the compounds (Zr, Ti)2O4 [also referred to ZrTiO4 when XTi = 0.5] and ZrTi2 O6 (srilankite), which were previously regarded as the respective high- and low-temperature forms of z irconium-titanate, are both stable at high temperatures (< 1200°c), and are part of the same solid solution that is continuous with pressure. srilankite (xTi = 0.67) formed at 1440°C and 28 kbar in equilibrium with rutile. This is the first synthesis of the phase at high pressures under equilibrium conditions. The stability of srilankite at high pressures and temperatures in our experiments contrasts with earlier studies that proposed a hydrothermal origin for the m ineral, with an upper stability limit of 900°C. Our results, however, are consistent with the natural occurrence of srilankite in high-grade rocks such as eclogites, granulites, lamprophyres and chromitites. Our experiments show that the stability of zirconium titanate is also strongly dependent on oxygen fugacity.
Keywords: srilankite; (Zr,Ti)2O4; ZrTiO4; solid solution; phase diagram; high-pressure study